Lectures on Antitrust Economics, Chapter 2: Price Fixing - Michael D. Whinston (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2003)
In this chapter, we begin our discussion of antitrust economics by considering what many consider its most central element: its ban on "price fixing" - that is, agreements among competitors over the prices they will charge or the outputs they will produce. Indeed, the prohibition on price fixing is one area of antitrust law that even those generally skeptical of governmental compe- tition policy typically regard approvingly. Nevertheless, despite its current uncontroversial status, we shall see that some significant and challenging open questions remain in this area.
Keywords: 330; Konzentrationspolitik; Kartellrecht; Preisabsprache; Fusionskontrolle; USA